Dental Autopsi dalam Bidang Kedokteran Gigi Forensik - Tanjung, Rizki (Jurnal Kedokteran Gigi Terpadu, 2024)
Introduction: Forensic Odontology (OF) is a branch of dentistry that deals with the legal field. Forensics is concerned with the identification process, which can be done with dental autopsies. Dental autopsy is in the form of a postmortem examination of the cadaver teeth to determine the cause of death and identify the victim. Discussion: The process of conducting an autopsy is regulated in laws, government regulations, and a circular letter of the minister of health that explains the rules and types of autopsy actions. The process of implementing dental autopsy must be carried out gradually and regularly. In addition, good visibility is needed to provide accurate results and maintain data accuracy, so specific techniques such as incision and excision methods are needed. Completeness of antemortem and postmortem data is also needed so that the identification process can run properly and precisely. Conclusion: Forensic odontology plays an important role in identifying unknown bodies through the estimation of age, gender, race, and abnormalities present in the teeth. This makes dental autopsy key in the current process of identifying and presenting dental evidence. However, there are still many public views that are still inaccurate and have the potential to hinder the identification process in forensic autopsy.